2021
DOI: 10.1038/s41467-021-22139-7
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the FOXA1 cistrome in treatment-emergent neuroendocrine prostate cancer

Abstract: Lineage plasticity, the ability of a cell to alter its identity, is an increasingly common mechanism of adaptive resistance to targeted therapy in cancer. An archetypal example is the development of neuroendocrine prostate cancer (NEPC) after treatment of prostate adenocarcinoma (PRAD) with inhibitors of androgen signaling. NEPC is an aggressive variant of prostate cancer that aberrantly expresses genes characteristic of neuroendocrine (NE) tissues and no longer depends on androgens. Here, we investigate the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 80 publications
5
99
0
Order By: Relevance
“…ChIP-seq experiments have demonstrated that FOXA1, a co-factor with both pioneering and transcription functions, binds to distinct sites and has different protein interactions that is dependent on the disease stage and pathological phenotype (Baca et al, 2021;Pomerantz et al, 2015;Pomerantz et al, 2020). Recent studies indicate that genomic alterations of FOXA1 promote ART resistance (Adams et al, 2019;Baca et al, 2021;Parolia et al, 2019;Shah and Brown, 2019). We have shown FOXA1 function remains functionally relevant even as mCRPC differentiate into aggressive variants that no longer require AR signaling, such as neuroendocrine prostate cancer (Baca et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…ChIP-seq experiments have demonstrated that FOXA1, a co-factor with both pioneering and transcription functions, binds to distinct sites and has different protein interactions that is dependent on the disease stage and pathological phenotype (Baca et al, 2021;Pomerantz et al, 2015;Pomerantz et al, 2020). Recent studies indicate that genomic alterations of FOXA1 promote ART resistance (Adams et al, 2019;Baca et al, 2021;Parolia et al, 2019;Shah and Brown, 2019). We have shown FOXA1 function remains functionally relevant even as mCRPC differentiate into aggressive variants that no longer require AR signaling, such as neuroendocrine prostate cancer (Baca et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
“…FOXA1 functions as an oncogenic pioneering and transcription factor in cancers, including prostate and breast (Gerhardt et al, 2012;Nakshatri and Badve, 2009;Shah and Brown, 2019). FOXA1 is a critical dependency in prostate cancer cell line models (Pomerantz et al, 2015), including those that transdifferentiate into AR-agnostic, neuroendocrine like features (Baca et al, 2021). Studies have broadly examined the binding patterns of FOXA1 with transcription regulatory elements in normal prostate tissue, primary prostate cancer, mCRPC, and neuroendocrine prostate cancers (Baca et al, 2021;Pomerantz et al, 2015;Pomerantz et al, 2020), demonstrating transcriptional programs associated with prostate in development, tumor progression and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With exception of loss of PTEN, RB1 and TP53, genomic analyses have not clarified genomic features that reliably distinguish these phenotypes or that can be used to predict risk of conversion to AR-null or NE-positive states. Epigenetic alterations, including changes in DNA methylation, chromatin accessibility, SWI/SNF, and histone markers are distinguishing features of NEPC, suggesting a key role of epigenetics in driving prostate cancer adenocarcinoma to NEPC (Dardenne et al 2016, Cyrta et al 2020, Baca et al 2021. Activation and coordination of lineage determining transcription factors (e.g.…”
Section: Emergence Of Aggressive Variant Prostate Cancermentioning
confidence: 99%
“…Activation and coordination of lineage determining transcription factors (e.g. ASCL1, BRN2, ONECUT2, MYCN, FOXA1) (Lee et al 2016, Bishop et al 2017, Guo et al 2019, Baca et al 2021) and pluripotency factors (e.g. SOX2) (Bishop et al 2017) and downregulation of REST (Zhang et al 2015) appear to drive lineage programming.…”
Section: Emergence Of Aggressive Variant Prostate Cancermentioning
confidence: 99%